(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article examines the prospects for increasing investment flows in the development of regional economies based on scientific and economic approaches and official statistical data. The study analyzes the theoretical foundations of regional investment policy, the role of investment attractiveness in ensuring sustainable economic growth, and the impact of foreign and domestic investments on regional socio-economic development. Particular attention is paid to the reforms implemented in Uzbekistan aimed at improving the investment climate, developing infrastructure, and expanding regional economic potential. In addition, the article evaluates advanced international experience in attracting investments and identifies the main factors influencing regional investment competitiveness. Based on the analysis, practical recommendations are proposed to improve the efficiency of investment policy, strengthen regional investment attractiveness, and ensure balanced economic development across regions.